Performance profiling in sports coaching: a review - Butterworth, A.; O'Donoghue, P.; Cropley, B. (International Journal of Performance Analysis in Sport, 2013)
Performance profiles have been developed to provide a collection of information about sports performances. The developments in the area include presentation methods for profiles and ways of interpreting performance indicator values within profiles. However, performance profiles need to be considered in the context of sports coaching. This paper presents a review of performance profiling techniques within the coaching process. The information needs of coaches attempting to manage this inherently complex process need to be served by performance analysis and performance profiles fulfil part of this role. The types of information used within coaching are reviewed before performance profiling techniques are critically examined with respect to coaching information needs. The review leads to the listing of a set of criteria for performance profiling techniques within sports coaching.